2020
DOI: 10.1055/a-1160-5917
|View full text |Cite
|
Sign up to set email alerts
|

Selektion von Intraokularlinsen bei Patienten mit Makulopathien

Abstract: Zusammenfassung Hintergrund Multifokale Intraokularlinsen (MIOLs) können Patienten in gewissem Maße Brillenunabhängigkeit bieten. In der Praxis stellt sich jedoch häufig die Frage, welche Patienten überhaupt für die Implantation von MIOLs geeignet sind. Nicht selten wird gezögert, MIOLs bei Patienten mit Makulopathien zu implantieren, da die Sorge besteht, dass die Multifokalität der implantierten IOL die Sehleistung dieser Patienten zusätzlich einschränkt. Ziel dieser Studie ist es, mittels virtuell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…U, Barcelona, Spain) allows the patient's defocusing curve for IOLs to be obtained. 21 , 23 , 25 However, some caution should be exercised when evaluating the results given that in VirtIOL experiments, the monofocal IOL achieved relatively good results at distances, 21 which does not correspond to clinical experience. Additionally, as this device is immobile, it is impossible to see the real world, and the patient can only see a simple target.…”
Section: Discussionmentioning
confidence: 99%
“…U, Barcelona, Spain) allows the patient's defocusing curve for IOLs to be obtained. 21 , 23 , 25 However, some caution should be exercised when evaluating the results given that in VirtIOL experiments, the monofocal IOL achieved relatively good results at distances, 21 which does not correspond to clinical experience. Additionally, as this device is immobile, it is impossible to see the real world, and the patient can only see a simple target.…”
Section: Discussionmentioning
confidence: 99%
“…Other conditions such as patients operated on with a monofocal IOL in the fellow eye, previous corneal refractive surgery with excimer laser, age over 75 years, or amblyopia have been also suggested to be relative contraindications to multifocality as the implantation of a multifocal IOL can compromise the patient's visual quality due to more di culty in the neuroadaptation ability or a baseline already compromised visual function [31]. Alternatives such as monovision or EDOF IOLs [20][21][22] have been described for this typology of patients. It should be considered that EDOF IOLs were designed with the aim of reducing dysphotopsia, with less reduction in contrast sensitivity [2][3][4][5][6][7][8][9][10][11][12] and higher tolerance to residual refractive errors than multifocal IOLs [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…To this date, very few studies have been conducted to evaluate the potential of EDOF IOLs for providing a successful visual restoration in those cases which the indication of multifocal IOLs is risky and not fully accepted [20][21][22]. The aim of the current study was to evaluate the visual and patient-reported outcomes of patients undergoing cataract surgery with implantation of an EDOF IOL who were not good candidates for multifocal IOL implantation due to one of the following conditions (common exclusion criteria of studies evaluating the outcomes of trifocal diffractive IOLs): patients operated on with a monofocal IOL in the fellow eye, previous corneal refractive surgery with excimer laser, mild and non-progressive maculopathy, mild and non-progressive glaucoma, age over 75 years, amblyopia, or previous vitrectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Although traditional thinking would typically exclude patients with macular pathology from multifocal technology, some studies have suggested that these patients can still benefit. 1,2…”
Section: Iqbal Ike K Ahmed MD Frcscmentioning
confidence: 99%